Modelling the effect of ageing on the yield strength of an aluminium alloy under cyclic loading at different ageing temperatures and test temperatures - Seisenbacher, B.; Winter, G.; Grün, F. (International journal of fatigue, 2020)
•Development of a new test strategy for efficient ageing tests.•With this test concept, the ageing could be investigated at different ageing and test temperatures.•This test concept allows the investigation of the influence of ageing on the deformation behaviour.•An ageing model was developed to be able to model the material behaviour. The simulation of engine components made of age-hardening materials which are subject to thermal–mechanical loads and in homogeneous thermal distribution, places high demands on the material model. To simulate such load cases, a model is required that allows us to consider the effects of ageing on the material properties along the entire temperature profile. This work presents an improved physical-based ageing model which takes different ageing and test temperatures into account. The improved model was fitted to Al-Si-Mg-Cu alloy data under uniaxial strain-controlled isothermal loading conditions at temperatures from room temperature to 250 °C. At the same ageing temperature and test temperature, the peak values of the simulation and test results were within ±2%. This improved model can serve as the basis for the cycle by cycle simulation of thermomechanical fatigue tests.